2020
DOI: 10.3390/en13071824
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Fusel Oil Features and Effect of Its Use in Different Compression Ratios for an SI Engine on Performance and Emission

Abstract: In this study, the effects of the use of improved fusel oil on engine performance and on exhaust emissions in a spark-ignition engine were investigated experimentally in consideration of the water, gum, and moisture content at high compression ratios according to TS EN 228 standards. In the study, a four-stroke, single-cylinder, air-cooled, spark plug ignition engine with an 8/1 compression ratio was used at three different compression ratios (8/1, 8.5/1, 9.12/1). Experiments were performed for six different r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 41 publications
0
3
0
2
Order By: Relevance
“…The main reason for lower HC emissions in ethanol-gasoline and methanol-gasoline blends is that ethanol and methanol contain an excessive amount of oxygen molecules in their structure. NOX emissions occur as a result of the nitrogen in the air reacting with oxygen at high temperatures during the combustion process inside the engine cylinder (Fletcher et al, 1971;Şimşek et al, 2020). The alterations of the NOX emissions for all the tested fuel samples according to the engine load was presented in Figure 7.…”
Section: Resultsmentioning
confidence: 99%
“…The main reason for lower HC emissions in ethanol-gasoline and methanol-gasoline blends is that ethanol and methanol contain an excessive amount of oxygen molecules in their structure. NOX emissions occur as a result of the nitrogen in the air reacting with oxygen at high temperatures during the combustion process inside the engine cylinder (Fletcher et al, 1971;Şimşek et al, 2020). The alterations of the NOX emissions for all the tested fuel samples according to the engine load was presented in Figure 7.…”
Section: Resultsmentioning
confidence: 99%
“…Silindir içerisinde yanma sonu oluşan yüksek sıcaklık ve yakıt içerisindeki oksijen miktarı CO2 oluşumunu tetikler [18,31,44]. Literatürdeki benzer çalışmalarda CO2 miktarının arttığı tespit edilmiştir [27,34,41,42]. Yapılan çalışmada %15'lik fuzel yağı katkısı yakıt karışımının içeriğindeki oksijen miktarının artışına sebep teşkil etmiş olabilir.…”
Section: Co2 Değişimleri (Co2 Changes)unclassified
“…Fuzel yağının fiziksel ve kimyasal özellikleri (Physical and chemical properties of fusel oil)[34] Test motoru teknik içerikleri (Test engine specifications) yağı ve benzin karışımları içerisindeki oktan sayısı üzerindeki baskın ısıl değerin etkisinin azalmasının etkisi olarak değerlendirilebilir[37].…”
unclassified
“…When the literature is searched, it is found that fusel oils are usually tested by mixing with gasoline fuel instead of diesel fuel. 40,41 There are a few studies investigating the effects of using fusel oil as an oxygenated fuel additive for diesel engines. So, the use of fusel oil as an alternative fuel in diesel engines can be considered as a new energy source for internal combustion engines.…”
Section: Introductionmentioning
confidence: 99%